Quantum Crystallography: Current Developments and Future Perspectives. Issue 43 (13th July 2018) - Genoni, Alessandro; Bučinský, Lukas; Claiser, Nicolas; Contreras‐García, Julia; Dittrich, Birger; Dominiak, Paulina M.; Espinosa, Enrique; Gatti, Carlo; Giannozzi, Paolo; Gillet, Jean‐Michel; Jayatilaka, Dylan; Macchi, Piero; et al.
Abstract: Crystallography and quantum mechanics have always been tightly connected because reliable quantum mechanical models are needed to determine crystal structures. Due to this natural synergy, nowadays accurate distributions of electrons in space can be obtained from diffraction and scattering experiments. In the original definition of quantum crystallography (QCr) given by Massa, Karle and Huang, direct extraction of wavefunctions or density matrices from measured intensities of reflections or, conversely, ad hoc quantum mechanical calculations to enhance the accuracy of the crystallographic refinement are implicated. Nevertheless, many other active and emerging research areas involving quantum mechanics and scattering experiments are not covered by the original definition although they enable to observe and explain quantum phenomena as accurately and successfully as the original strategies. Therefore, we give an overview over current research that is related to a broader notion of QCr, and discuss options how QCr can evolve to become a complete and independent domain of natural sciences. The goal of this paper is to initiate discussions around QCr, but not to find a final definition of the field. Abstract : Between Two Worlds—A New World : An amalgamation of quantum mechanics and diffraction experiments is a magnifying lens for the quantum phenomena in molecules and materials. In this Review, the new research domain "quantum crystallography" is debated in the context of current research fields. The perspective of becoming an independent natural science is outlined.